2022
DOI: 10.1039/d2en00376g
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional dual emissive fluorescent probe based on europium-doped carbon dots (Eu-TCA/NCDs) for highly selective detection of chloramphenicol, Hg2+ and Fe3+

Abstract: Lanthanide functionalized N-doped carbon dots have potential application in the development of innovative photoluminescence probes for biological analytes. In this study, a novel multifunctional dual-emissive fluorescent probe based on europium...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…230,231 Recently, our group reported the synthesis and sensing application of carbon dots-based fluorescent probes which illustrate the applicability of carbon dots in fluorescence sensing. 232,233 The above results show that both organic dyes and nanomaterials make it possible to develop novel practical fluorescent G4 platforms in cells, which is useful in cancer therapy.…”
Section: Gfs Based On Nanomaterials and G4 For Detecting Metal Ions A...mentioning
confidence: 84%
See 1 more Smart Citation
“…230,231 Recently, our group reported the synthesis and sensing application of carbon dots-based fluorescent probes which illustrate the applicability of carbon dots in fluorescence sensing. 232,233 The above results show that both organic dyes and nanomaterials make it possible to develop novel practical fluorescent G4 platforms in cells, which is useful in cancer therapy.…”
Section: Gfs Based On Nanomaterials and G4 For Detecting Metal Ions A...mentioning
confidence: 84%
“…The high stability of nanomaterials is referenced in the previous section. For example, carbon dots with exceptional optical characteristics, high stability, and biocompatibility have potential value for developing novel GFS. , Recently, our group reported the synthesis and sensing application of carbon dots-based fluorescent probes which illustrate the applicability of carbon dots in fluorescence sensing. , The above results show that both organic dyes and nanomaterials make it possible to develop novel practical fluorescent G4 platforms in cells, which is useful in cancer therapy.…”
Section: Summary and Outlookmentioning
confidence: 89%
“…Based on this principle, many lanthanide-based fluorescent probes have been developed in recent years, including the sensor of Hg 2+ ions. 154–162…”
Section: Fluorescent Sensors Involved In the Lmet Processmentioning
confidence: 99%
“…Based on this principle, many lanthanide-based uorescent probes have been developed in recent years, including the sensor of Hg 2+ ions. [154][155][156][157][158][159][160][161][162] In 2010, Liu et al 163 reported for the rst time a highly selective Hg 2+ ion probe based on the lanthanide complex. They designed and synthesized novel pendant benzo crown ether using a benzo-15-crown-5 unit as a macrocyclic receptor and Nbenzylsalicylamide as a chromophore and coordination unit.…”
Section: Fluorescent Sensors Involved In the Lmet Processmentioning
confidence: 99%
“…5,6 Various forms of carbon materials like graphene, fullerene, carbon nanotubes, and carbon dots have been developed to be exploited in sensing, bioimaging, drug delivery, tumor theranostics, etc. [7][8][9][10] Recently, carbon-based nanomaterials have gained a lot of attention as drug immobilization carriers. 11 Formerly, Prylutska S. V. et al reported the viability of a C 60 composite with doxorubicin (DOX) as a new chemotherapeutic agent that successfully kills tumour cells or tissues while avoiding the adverse reactions of DOX in its free form on normal cells.…”
Section: Introductionmentioning
confidence: 99%